If it's not what You are looking for type in the equation solver your own equation and let us solve it.
10-3x=-5x+6
We move all terms to the left:
10-3x-(-5x+6)=0
We get rid of parentheses
-3x+5x-6+10=0
We add all the numbers together, and all the variables
2x+4=0
We move all terms containing x to the left, all other terms to the right
2x=-4
x=-4/2
x=-2
| 3+5-x=-x=-7 | | 100=6c+4c | | 6c+4c=100 | | 45=x-20= | | 10÷x=4÷7 | | 9m=81,m=3,9,-3 | | m=3,9,-3 | | -9x5=32 | | 28-y-y=7 | | Y+10+y=44 | | 4b+7=41 | | 2u+2u-16=-16 | | 11n-n^2=24 | | 2x+6+6x+-22=90 | | 18.2=y-11=y | | 25/5÷x=50 | | 3/5x+2/3x=23 | | 10+y=44+y | | 3(z-2)+6=5(z4 | | 5x-7=8x+9 | | -4=k+3.5 | | 5y^2-13=0 | | 10+y.y=44 | | 16-5n=1 | | 2y-54=-y+21 | | 4b-10=22 | | 2=|r-7| | | K/8-k=-20 | | -4a-1=-1+7aa= | | 3x-9=5x-4x= | | M4=m-11 | | 1x=0x |